1996
DOI: 10.1056/nejm199603143341102
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Venous Thrombosis with Intravenous Unfractionated Heparin Administered in the Hospital as Compared with Subcutaneous Low-Molecular-Weight Heparin Administered at Home

Abstract: In patients with proximal-vein thrombosis, treatment with low-molecular-weight heparin at home is feasible, effective, and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
602
3
43

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,086 publications
(667 citation statements)
references
References 26 publications
19
602
3
43
Order By: Relevance
“…Moreover, two major RCTs have also established that the outpatient administration of LMWH is as safe as unfractionated heparin administered in hospital for the treatment of DVT [42][43][44]. For these reasons, outpatient treatment of patients with DVT, with or without asymptomatic PE, has become common practice worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two major RCTs have also established that the outpatient administration of LMWH is as safe as unfractionated heparin administered in hospital for the treatment of DVT [42][43][44]. For these reasons, outpatient treatment of patients with DVT, with or without asymptomatic PE, has become common practice worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acute deep vein thrombus (DVT) can safely be treated as outpatients [1][2][3][4]. Outpatient treatment of DVT is recommended with grade 1B evidence in the most recent American College of Chest Physicians (ACCP) guidelines [5].…”
Section: Introductionmentioning
confidence: 99%
“…Both studies showed a similar frequency of recurrent tromboembolic events and bleeding com plications. In conclusion treatment with LMWH at home seems feasible, effective and safe [46][47][48]. This change from hospital to community care might overlook two important achievements of recent years.…”
Section: Low Molecular Weight Heparins (Lmwh)mentioning
confidence: 97%
“…Table 1 shows the different LMWH that are currently registered for treatment of DVT in the Netherlands. Jn conclusion, LMWH seem promising for the initial treatment of DVT and are about to replace intravenous heparin treatment [20], Recently evi dence has been provided that in the future patients with DVT might even be treated with LMWH at home [46,47], Both studies compared treatment with SH (administered in the hospital intravenously) to LMWH. The studies allowed outpatients taking LMWH to go home immediately and hospitalized patients taking LMWH to be discharged early.…”
Section: Low Molecular Weight Heparins (Lmwh)mentioning
confidence: 99%
See 1 more Smart Citation